Pengaruh Intensitas Penggunaan Dance Challenge TikTok terhadap Interaksi Sosial Remaja di SMPN 15 Banjarmasin - Rahmadianty, Pritha; Khairussalam (Huma: Jurnal Sosiologi, 2025)
In the era of globalization marked by rapid technological developments, social media such as TikTok has become a popular platform that allows unlimited interaction through short video trends such as dance challenges that are popular with teenagers because of their entertaining nature while encouraging collaboration and social interaction. The purpose of this study was to determine the effect of the intensity of TikTok dance challenge use on the social interaction of teenagers at SMPN 15 Banjarmasin. An associative quantitative approach was used in this study, with a data collection technique using a questionnaire. Data analysis used simple linear regression. The results showed that there was a significant effect between the intensity of TikTok dance challenge use on the social interaction of teenagers at SMPN 15 Banjarmasin. This can be seen from the significance value of 0.000 <0.05, thus the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The regression equation obtained Y = 5.015 + 0.765X. The R Square (R²) value is 0.660. 66% of social interaction variables are influenced by the intensity of TikTok dance challenge use, the remaining 34% are influenced by other factors. This study adds a new perspective compared to previous studies. By exploring the dance challenge trend, this study provides deeper insights into how creative and participatory activities on TikTok, such as dancing, can influence the way teenagers interact. It is hoped that further research will involve more schools and integrate qualitative approaches to gain a deeper and more comprehensive understanding of the phenomenon studied.